Demon theory - Jones, Stephen Graham 1972- (MacAdam/Cage, 2006)
Jones details the horrifying events set in motion by a tragic childhood incident. When med student Hale is called home by his ailing mother on Halloween night, he and a group of friends are trapped in an inescapable cycle of violence